Konsep dan Praktik Arisan online “Awrisan MBabel 88” Dalam Perspektif Fikih Muamalah - Azzahra, Asy syifa; Hermawan, Aries (Department of Islamic Economics Law, 2024)
Online arisan has become popular in Indonesia, but the lack of understanding of sharia principles in this practice is a concern. The purpose of this study is to understand the implementation mechanisms and regulations in online arisan and identify relevant muamalah jurisprudence concepts, such as the validity of contracts and management transparency. This research method uses a qualitative approach through literature studies and field studies with researchers directly involved in the research location, namely the online social gathering activity Awrisan Mbabel 88. The results show that this social gathering is in accordance with the muamalah principle if the management of fine fees is not considered as the admin's personal income. Awrisan Mbabel 88 has implemented a qardh contract that is free from elements of riba or exploitation, although it is difficult to prove legally, this arisan focuses on the principles of help and kinship.